2021
DOI: 10.3390/molecules26092789
|View full text |Cite
|
Sign up to set email alerts
|

Antidementia Effects of Alternanthera philoxeroides in Ovariectomized Mice Supported by NMR-Based Metabolomic Analysis

Abstract: The crude ethanol extract of the whole plant of Alternanthera philoxeroides (Mart.) Griseb was investigated for its potential as antidementia, induced by estrogen deprivation, based on in vitro antioxidant activity, β-amyloid aggregation inhibition and cholinesterase inhibitory activity, as well as in vivo Morris water maze task (MWMT), novel object recognition task (NORT), and Y-maze task. To better understand the effect of the extract, oxidative stress-induced brain membrane damage through lipid peroxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 39 publications
(55 reference statements)
1
17
0
Order By: Relevance
“…They had noticed various mechanisms behind it like inhibition of lipid peroxidation in the whole brain, downregulation of neuroinflammatory cytokines (IL-1β, IL-6, and TNF-α), etc ( Khamphukdee et al, 2021 ). Phytomolecules like Luteolin and luteolin analogs ( Delgado et al, 2021 ), Vitexin ( Malar et al, 2020 ; Zhang et al, 2021 ), Quercetin ( Yao et al, 2010 ), Torosaflavone E ( Khamphukdee et al, 2021 ), Demethyl torosaflavone D ( Khamphukdee et al, 2021 ), β-Sitosterol ( Kim et al, 2008 ), Stigmasterol ( Park S. J. et al, 2012 ; Pratiwi et al, 2021 ), Ursolic acid ( Habtemariam, 2019 ), Oleanolic acid and oleanolic acid analogs ( Lin et al, 2021 ), Caffeic acid ( Khan et al, 2013 ; Deshmukh et al, 2016 ), Quinic acid ( Liu et al, 2020 ), p-Coumaric acid ( Kim H.-B. et al, 2017 ), β-Carboline ( Zhao et al, 2013 ; Li et al, 2018 ), Malic acid ( Tian et al, 2021 ), Blumenol A ( Emir et al, 2019 ), Phytol ( Sathya et al, 2020 ), and Pheophytin A ( Park et al, 2014 ) which were earlier reported from Alternanthera philoxeroides (Mart.)…”
Section: Introductionmentioning
confidence: 99%
“…They had noticed various mechanisms behind it like inhibition of lipid peroxidation in the whole brain, downregulation of neuroinflammatory cytokines (IL-1β, IL-6, and TNF-α), etc ( Khamphukdee et al, 2021 ). Phytomolecules like Luteolin and luteolin analogs ( Delgado et al, 2021 ), Vitexin ( Malar et al, 2020 ; Zhang et al, 2021 ), Quercetin ( Yao et al, 2010 ), Torosaflavone E ( Khamphukdee et al, 2021 ), Demethyl torosaflavone D ( Khamphukdee et al, 2021 ), β-Sitosterol ( Kim et al, 2008 ), Stigmasterol ( Park S. J. et al, 2012 ; Pratiwi et al, 2021 ), Ursolic acid ( Habtemariam, 2019 ), Oleanolic acid and oleanolic acid analogs ( Lin et al, 2021 ), Caffeic acid ( Khan et al, 2013 ; Deshmukh et al, 2016 ), Quinic acid ( Liu et al, 2020 ), p-Coumaric acid ( Kim H.-B. et al, 2017 ), β-Carboline ( Zhao et al, 2013 ; Li et al, 2018 ), Malic acid ( Tian et al, 2021 ), Blumenol A ( Emir et al, 2019 ), Phytol ( Sathya et al, 2020 ), and Pheophytin A ( Park et al, 2014 ) which were earlier reported from Alternanthera philoxeroides (Mart.)…”
Section: Introductionmentioning
confidence: 99%
“…Previous works from different groups have shown that OVX induces neuroinflammation (overproduction of inflammatory cytokines and glial activation in CNS) and/or memory decline, depression-like behaviors in mice, [45][46][47][48][49][50][51][52][53] and in rats. [54][55][56][57][58] Consistently, in the present work we found that chronic pain and memory/emotional deficits were associated with neuroinflammation in OVX and aged female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although A. philoxeroides is considered as an obnoxious invasive weed around the globe, because of its long-standing traditional medicinal uses, particularly against various viral infectious diseases, this plant and its secondary metabolites have been subjected to various bioactivity studies, revealing the therapeutic potential of this species [2][3][4][5][6][7][8][9][10][11][12][13][16][17][18]29,43,44,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91], particularly as an antiviral agent (Table 1).…”
Section: Bioactivities and Therapeutic Potential As An Antiviral Agentmentioning
confidence: 99%
“…Several plant products (e.g., Ginkgo biloba extract, ginseng extract, coconut oil, omega-3 fatty acids, curcumin, and resveratrol, and vitamins (e.g., vitamin B 12 and vitamin D) have long been used for the prevention and treatment of dementia [77]. Khamphukdee et al [78] recently evaluated an EtOH extract of the whole plant of A. philoxeroides for its potential in the treatment of dementia, using various assays including in vitro antioxidant assays, β-amyloid aggregation inhibition, and cholinesterase inhibitory activity assays as well as an in vivo Morris water maze task, novel object recognition task, and Y-maze task assays. The extract as well as its flavonoids (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) offered inhibition of β-amyloid aggregation.…”
Section: Antidementia Activitymentioning
confidence: 99%
See 1 more Smart Citation